2020
DOI: 10.33448/rsd-v9i7.4187
|View full text |Cite
|
Sign up to set email alerts
|

Subprodutos da soja na alimentação de aves: Revisão

Abstract: The use of soy by-products in poultry feed has proven to be an important sustainable alternative, being capable of minimizing the environmental damage caused by the disposal of these residues and at the same time reducing the cost of production. However, for the use of these by-products in poultry feeding, it is necessary to know their chemical composition, antinutritional factors and also necessary measures to reduce these factors, as well as the best levels of inclusion that must meet the nutritional require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
0
0
3
Order By: Relevance
“…Nitrogen is one of the main pollutants in pig manure, which can be applied to poultry manure. The results of previous studies have demonstrated that in the pre-initial period from four to seven days, the addition of both powdered and liquid cellulase enzyme significantly reduced nitrogen excretion, improving nutrient utilization [28,29]. A similar result was found in reference [30].…”
Section: Discussionmentioning
confidence: 55%
“…Nitrogen is one of the main pollutants in pig manure, which can be applied to poultry manure. The results of previous studies have demonstrated that in the pre-initial period from four to seven days, the addition of both powdered and liquid cellulase enzyme significantly reduced nitrogen excretion, improving nutrient utilization [28,29]. A similar result was found in reference [30].…”
Section: Discussionmentioning
confidence: 55%
“…A soja (Glycine max) é uma das principais leguminosas produzidas no mundo, devido ao elevado potencial de produção e valor nutritivo, podendo ser utilizada na nutrição humana e animal, possuindo papel de destaque na economia brasileira (Gouveia et al, 2020). A produção mundial foi 348,7 milhões de toneladas, sendo que o Brasil produziu 117,8 milhões de toneladas, se tornando o segundo maior produtor mundial (Fao, 2020).…”
Section: Introductionunclassified
“…O aumento do consumo dessa commodity causa alterações em seus preços, trazendo impacto ao orçamento dos brasileiros. O milho como fonte de energia e a soja como fonte de proteína (Gouveia, de Paulo, da Silva, de Sousa, dos Santos, & Minafra, 2020) são os principais insumos utilizados na formulação das rações de frangos de corte (Oliveira Júnior, Wander, & Figueiredo, 2014).…”
Section: Introductionunclassified